2020
DOI: 10.1007/s11135-020-00985-9
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of social media usage, political learning and participation among youth: a comparative study of Indonesia and Pakistan

Abstract: Youth participation in political matters has gained attention among people around the globe where youth involvement in certain political activities has been witnessed (of public in Indonesia and Pakistan). Keeping in view this scenario, the current study aimed to identify the sway of social media in enhancing youth involvement in political learning, political participation and political efficacy. This quantitative study was conducted through online and offline survey in both countries at the time of general el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 33 publications
2
29
0
3
Order By: Relevance
“…This shows that news media has direct impacts on social capital. These findings have not only supported the hypothesis 2 but also in line with the previous studies findings (Ohme, 2020;Ida, Saud, 2020;Lu, Lee, 2021;Uslaner, 1998), who in their study also found news media as a significant predictor of social capital. In this regard, the present study testifies the results of previous literature.…”
Section: Discussionsupporting
confidence: 91%
“…This shows that news media has direct impacts on social capital. These findings have not only supported the hypothesis 2 but also in line with the previous studies findings (Ohme, 2020;Ida, Saud, 2020;Lu, Lee, 2021;Uslaner, 1998), who in their study also found news media as a significant predictor of social capital. In this regard, the present study testifies the results of previous literature.…”
Section: Discussionsupporting
confidence: 91%
“…Table 2 further shows that more than one-third of the respondents (39.6%) are likely to do this. The role of social media is not only about sharing information; however, it also solidifies the efficacy of social media users when it comes to politics (Ida et al 2020). According Table 2, it can be concluded that most general (for open and analytical reasons) social media that is used for learning and participating for a political purpose may be supportive.…”
Section: Opinion About the Usage Of Social Media For Politicsmentioning
confidence: 99%
“…Youth worldwide use social media outlets to get political information (Yamamoto et al, 2020) and are more likely to react to political content (Jeroense et al, 2021). Ida et al (2020) researched the relationship between social media and youth involvement in political learning, participation, and efficacy. They collected data from Pakistan and Indonesia through online and offline surveys.…”
Section: Literature Reviewmentioning
confidence: 99%